2011
DOI: 10.1086/658673
|View full text |Cite
|
Sign up to set email alerts
|

SYNAPPS: Data-Driven Analysis for Supernova Spectroscopy

Abstract: We introduce a new computer program, SYNAPPS, for forward-modeling of supernova (SN) spectroscopy data sets. SYNAPPS is a spectrum fitter embedding a highly parameterized synthetic SN spectrum calculation within a parallel asynchronous optimizer. This open-source code is primarily aimed at the problem of systematically interpreting large sets of SN spectroscopy data. While SYNAPPS should be useful to current SN spectroscopy efforts like the Nearby Supernova Factory, Lick Observatory Supernova Search, Palomar T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
192
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(211 citation statements)
references
References 18 publications
(18 reference statements)
16
192
0
3
Order By: Relevance
“…Additional study and confirmation was performed by Syn++ (Thomas et al 2011) modeling of a few of the optical spectra as shown in Figure 19. While the synthetic modeling produces most of the ionic signatures, the most obvious Hα profile is not reproduced.…”
Section: Line Identification and Spectrum Modelingmentioning
confidence: 99%
“…Additional study and confirmation was performed by Syn++ (Thomas et al 2011) modeling of a few of the optical spectra as shown in Figure 19. While the synthetic modeling produces most of the ionic signatures, the most obvious Hα profile is not reproduced.…”
Section: Line Identification and Spectrum Modelingmentioning
confidence: 99%
“…To estimate line velocities of select atomic species, we utilize the fast and highly parameterized spectrum synthesis code, SYNAPPS (Thomas et al 2011b). The SYNAPPS model, formerly SYNOW (Fisher 2000), assumes spherical symmetry, a sharp photosphere, pure resonance line scattering treated under the Sobolev approximation, and Boltzmann statistics for electron level populations (parameterized by temp in SYNAPPS).…”
Section: The Synapps Modelmentioning
confidence: 99%
“…In SYNAPPS, quadratic warping constants a0, a1, and a2 supplement t phot to form a more flexible continuum reference level; a0, a1, a2, and t phot form the backbone to data-driven minimization. (See Thomas et al 2011b and Fig. 2 of Parrent et al 2012 for an example.…”
Section: The Synapps Modelmentioning
confidence: 99%
“…We applied the parameterized resonance scattering code SYN++ in combination with SYNAPPS 3 (Thomas, Nugent & Meza 2011) to model the spectroscopic evolution of SN 2013df (hereafter we refer only to SYNAPPS). Detailed spectral modelling based on this code -or on SYNOW, the original version of these kind of codes (see e.g.…”
Section: Spectral Modellingmentioning
confidence: 99%